Managing Phase Orientation and Crystallinity of Printed Dion-Jacobson 2D Perovskite Layers via Controlling Crystallization Kinetics - Chen, Yijun; Hu, Jinlong; Xu, Zhenhua; Jiang, Zhengyan; Chen, Shi; Xu, Baomin; Xiao, Xiudi; Liu, Xianhu; Forberich, Karen; Brabec, Christoph; Mai, Yaohua; Guo, Fei (Advanced Functional Materials, 2022)
Two-dimensional perovskites have attracted substantial attention for solar cell applications because of their higher stability as compared to their 3D analogs. To achieve efficient charge transport in thin-film devices, obtaining high crystalline perovskite crystals perpendicularly aligned to the substrate is of great importance. This article reports the scalable printing of high-quality Dion-Jacobson (DJ) perovskite thin films via tailoring crystallization kinetics. Introducing a small amount of 1-methyl-2-pyrrolidinone to the conventional N,N-dimethylformamide:dimethyl sulfoxide-based precursor, the strong coordination with ammonium spacers enables a notably retarded crystallization, which results in perovskite films with distinctly enhanced crystallinity, highly vertical orientation, and graded phase distribution. Accordingly, efficient charge generation and ultrafast interphase charge transfer are realized. The champion DJ perovskite device delivers a high current density of 17.10 mA cm(-2), an impressive open-circuit voltage of 1.21 V, leading to a stabilized efficiency of 16.19%. In addition, the devices processed from the ternary solvent exhibit remarkably improved stability under stimuli with light, heat, and humidity, benefiting from their superb phase stability. This work demonstrates an important advancement in scalable deposition of DJ perovskite thin films for efficient and stable photovoltaic devices.
CRIS-Team WoS Importer:2022-02-18